The Usability Paradigm in Passwordless Authentication : A Comparative Study of YubiKey and Passkey Implementations - Sharath Chandra Thurupati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The widespread adoption of passwordless authentication methods, such as YubiKey and passkeys, represents a significant shift in Identity and Access Management (IAM) systems. While these technologies offer enhanced security by mitigating vulnerabilities associated with traditional passwords, their success hinges on effectively balancing robust security with user experience and accessibility. This article comprehensively analyzes YubiKey and passkey implementations, examining their impact on user interaction, cross-platform compatibility, and setup processes. We explore critical accessibility considerations, including challenges faced by users with physical disabilities and the inclusivity of biometric systems. The article also investigates the delicate balance between security and convenience, emphasizing the importance of user education and support in fostering adoption. By evaluating current implementations and projected technological advancements, we provide insights into the future landscape of passwordless authentication. Our findings underscore the crucial role of user-centric design in developing secure, accessible, and inclusive authentication systems, paving the way for a more secure and user-friendly digital ecosystem.
Keywords: Passwordless Authentication; User Experience; Accessibility; YubiKey; Passkeys